The God on the Windy Tree: Christian Origins of the Figure of Wodan in the Cross-cultural Relations of Northern Europe - Strijen, Bob Oscar Benjamin van (2016)
The myth of Óðinn hanging on the tree resembles, in a number of ways, the legend of Christ hanging on the Cross―self-sacrifice and wounding by a spear for example. Scholarship has largely focussed on these parallels, particularly whether the Scandinavian myth―as currently known―had original pre-Christian pagan roots or had a medieval Christian overlay. Scholars have not come to a consensus on whether the myth of Óðinn was coloured in the Christian contexts of the Danelaw or Iceland, or if the hanging referred, perhaps, to an ancient pagan initiation ritual involving a god similar to Mercurius, as described by Tacitus. This study seeks to examine a third option. In a broad historiographical survey, I evaluate the earliest evidence―runic inscriptions, bracteates, and, to some extent, Anglo-Saxon royal genealogies and place-names―for the god Wodan, a continental cognate of Óðinn, as well as for his equation with the Roman god Mercury. Here, I find that the former does not predate the fifth century at the earliest, whereas the latter happened in the seventh century. Additionally, I assess the rise of Christianity in the Roman Empire and the spread of Christianity and Roman influences to northern Europe. I find here that, firmly established on the limites of the Empire at the beginning of the fourth century, Christianity must have been present in the minds of the Germanic peoples in the border regions. Through trade routes, furthermore, Roman influence reached even further north. It is, then, possible that these Germanic peoples adopted and remodelled Christ and his religion into the pagan cult of Wodan, before the missions started to properly convert these heathens in the North.